Commitment and sacrifice in emerging adult cyclical and non-cyclical romantic relationships - Monk, James Kale (Kansas State University, 2013)
Patterns in, and quality of, early romantic relationships have been found to impact future relationship outcomes (Donnellan et al., 2005; Overbeek et al., 2007). Commitment and satisfaction with sacrifice have been cited as important constructs in relationship health and stability as they indicate investment in the relationship (Stanley & Markman, 1992; Rusbult, 1983). Little research has been done on the bi-directional relationship of these two constructs. Many authors indicate that commitment predicts sacrifice (e.g. Van Lange, Rusbult, et al., 1997), but others argue that sacrifice predicts subsequent commitment (e.g. Kelley, 1979). The purpose of this study was to explore the time-ordering of these constructs and whether a history of relationship breakup and renewal (termed cyclicality) moderated this relationship in an emerging adult population (n = 246). Using a cross-lagged model over three time points, the present study found support for a bi-directional relationship between commitment and satisfaction with sacrifice that was not moderated by a history of cyclicality. However, partners with a history of breakup and renewal did report lower dedication at Time 3, indicated by a group mean difference. Implications for theory, research, and intervention are discussed.
Keywords: Commitment; Dedication; Emerging adult; Romantic relationships; Sacrifice; Instability; Individual & Family Studies (0628); Social Psychology (0451); Social Research (0344)